2020
DOI: 10.1002/alz.040473
|View full text |Cite
|
Sign up to set email alerts
|

A single ascending dose study in healthy volunteers to assess the safety and PK of LY3372689, an inhibitor of O‐GlcNAcase (OGA) enzyme

Abstract: Background LY3372689, an O‐GlcNAcase (OGA) enzyme inhibitor, is being developed as a potential treatment for tauopathies, including Alzheimer’s disease. OGA inhibition is proposed to delay the progression of tau‐related diseases by slowing the accumulation of hyper‐phosphorylated, insoluble tau filaments. Herein we report the first clinical study that assessed safety and pharmacokinetics (PK) of LY3372689 after single oral doses in healthy volunteers (HV). Method The phase 1 clinical trial (NCT03819270) was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition to their power to elucidate normal neurobiological processes, chemical methods show great promise in manipulating O−GlcNAc for future clinical benefit in nervous system injuries and pathologies. Recent studies have employed these tools to probe therapeutic potential in numerous disease models and human clinical trials [18,146–151] . In particular, there has been significant progress in the pharmacological targeting of O−GlcNAcylation on tau [88,89,38,90,91,63,92,93] and α‐synuclein [123–126] for AD, PD and related disorders.…”
Section: O−glcnacylation In Neurological Diseases: Dysregulation and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their power to elucidate normal neurobiological processes, chemical methods show great promise in manipulating O−GlcNAc for future clinical benefit in nervous system injuries and pathologies. Recent studies have employed these tools to probe therapeutic potential in numerous disease models and human clinical trials [18,146–151] . In particular, there has been significant progress in the pharmacological targeting of O−GlcNAcylation on tau [88,89,38,90,91,63,92,93] and α‐synuclein [123–126] for AD, PD and related disorders.…”
Section: O−glcnacylation In Neurological Diseases: Dysregulation and ...mentioning
confidence: 99%
“…These results led to Phase I human trials, which showed low toxicity in healthy volunteers [149] . Second, LY3372689 (Eli Lilly) has been tested as a potential treatment for AD and other tauopathies, with promising safety and pharmacokinetic parameters after single and multiple oral doses in healthy volunteers [146,147, 150] . Third, ASN90 (Asceneuron S.A.) potently inhibits rodent and human OGA, crosses the blood‐brain barrier, and exhibits favorable drug‐like properties for the central nervous system [39] .…”
Section: Oga Inhibitors As Drug Candidates For Human Neurodegenerationmentioning
confidence: 99%
“…The pharmacokinetics were deemed supportive of once-a-day dosing. 192 Two other Phase 1 studies were carried out to measure LY3372689 binding in the brain through displacement of the OGA-specific PET ligand 18 F-LSN3316612. 193 The primary outcome of the studies was the percent of OGA occupancy before and after dosing.…”
Section: Ly3372689mentioning
confidence: 99%
“…The drug appeared to be well tolerated at all doses, without serious adverse events or discontinuations due to adverse events. The pharmacokinetics were deemed supportive of once‐a‐day dosing 192 . Two other Phase 1 studies were carried out to measure LY3372689 binding in the brain through displacement of the OGA‐specific PET ligand 18 F‐LSN3316612 193 .…”
Section: Anti‐tau Drugsmentioning
confidence: 99%
“…For example, multiple reports showed that elevating O−GlcNAcylation via treatment with the small molecule OGA inhibitor Thiamet-G 69 reduced proteotoxicity, cognitive deficits, and behavioral dysfunction in AD rodent models 70,71 . Based on these and other promising pre-clinical data 68,72 , at least three OGA inhibitors (MK-8719, LY3372689, ASN90) have entered human clinical trials 73-75 , paving the way for future pharmacological modulation of O-GlcNAc on substrates, such as NF proteins, in human patients. However, despite its potential clinical significance, the functional impact of O-GlcNAcylation on human NF proteins has never been studied systematically.…”
Section: Introductionmentioning
confidence: 99%